A very massive spectroscopic binary in the LH 54 OB association in the Large Magellanic Cloud - Ostrov, Pablo Gabriel (2002)
We announce the discovery of a new early-type, double-lined spectroscopic binary in the LH 54 OB association in the Large Magellanic Cloud. We present a V light curve and radial velocities. We investigate the possible configurations of the system, concluding that it probably contains the most massive star measured at the present, with a mass of the order of 100 M⊙, while its companion has approximately 50 M⊙.